Role of methylated septin 9 as an adjunct diagnostic and prognostic biomarker in hepatocellular carcinoma. Issue 10 (October 2021) - Bannaga, Ayman S.; Alvarez, Rocio; Zhou, Lisa; Petchey, Michael; Noufaily, Angela; Hitchins, Megan P.; Arasaradnam, Ramesh P.
Abstract: Background: Methylated septin 9 (mSEPT9) has a role in hepatocarcinogenesis. We evaluated mSEPT9 performance in patients with hepatocellular carcinoma (HCC) and those at risk of HCC Methods: Using Epi-proColon® V2.0 assay adapted for 1 mL plasma, we investigated mSEPT9 sensitivity, specificity, associations with influential covariates and relation to death. Results: Of 141 participants included, 136 had liver disease, 38 with HCC (mean-age 71 years) and 103 without HCC (mean-age 56.8 years), with further five without liver disease. 41 patients died (23 HCC) by the end of the study follow-up period. In HCC, mSEPT9 sensitivity and specificity were 89.47% (CI:75.20%–97.06%) and 81.55% (CI:72.70%–88.51%), whilst alpha fetoprotein (AFP) sensitivity and specificity were 50% (CI:33.38%–66.62%) and 97.09% (CI:91.72%–99.40%), respectively. Age-adjusted logistic regression showed mSEPT9 was associated with age, body mass index, HCC, liver cirrhosis, AFP, platelets, neutrophil-to-lymphocyte-ratio, albumin-bilirubin grade and fibrosis-4 index (p < 0.05). Odds for HCC patients to have positive mSEPT9 were 27.4 times more than those without HCC. Time-to-death was associated with mSEPT9 positivity (p < 0.05). Kaplan–Meier curves showed higher HCC survival with mSEPT9 compared to AFP. Conclusions: The mSEPT9 offers potential diagnostic and prognostic biomarker for HCC. After adjusting for age, mSEPT9 remained associated with liver function, liver fibrosis and inflammatory surrogate markers. Graphical abstract: Image 1